Dose-response associations of cardiorespiratory fitness with all-cause mortality and incidence and mortality of cancer and cardiovascular and respiratory diseases: the UK Biobank cohort study. Issue 21 (November 2019) - Steell, Lewis; Ho, Frederick K; Sillars, Anne; Petermann-Rocha, Fanny; Li, Hiu; Lyall, Donald M; Iliodromiti, Stamatina; Welsh, Paul; Anderson, Jana; MacKay, Daniel F; Pell, Jill P; Sattar, Naveed; et al.
Abstract : Objective: To investigate the association of cardiorespiratory fitness with all-cause mortality, and cardiovascular disease (CVD), respiratory disease, chronic obstructive pulmonary disease (COPD) and cancer mortality and incidence. Design: Prospective population-based study. Setting: UK Biobank. Participants: Of the 5 02 628 (5.5% response rate) participants recruited by UK Biobank, we included 73 259 (14.6%) participants with available data in this analysis. Of these, 1374 participants died and 4210 developed circulatory diseases, 1293 respiratory diseases and 4281 cancer, over a median of 5.0 years (IQR 4.3–5.7) follow-up. Main outcome measures: All-cause mortality and circulatory disease, respiratory disease, COPD and cancer (such as colorectal, lung, breast and prostate) mortality/incidence. Fitness was estimated using a submaximal cycle ergometer test. Results: The HR for all-cause mortality for each metabolic equivalent of task (MET) higher fitness was 0.96 (95% CI 0.93 to 0.98). Similar results were observed for incident circulatory disease (HR 0.96 [0.95 to 0.97]), respiratory disease (HR 0.96 [0.94 to 0.98]), COPD (HR 0.90 [0.86 to 0.95) and colorectal cancer (HR 0.96 [0.92 to 1.00]). Nonlinear analysis revealed that a high level of fitness (>10METs) was associated with a greater incidence of atrial fibrillation (HR 1.24 [1.07 to 1.44]) and prostate cancer (HR 1.16 [1.02 to 1.32]) compared with average fitness. All results were adjusted for sociodemographic, lifestyle and dietary factors, body composition, and morbidity at baseline and excluded events in the first 2 years of follow-up. Conclusions: Higher cardiorespiratory fitness was associated with lower risk of premature mortality and incidence of CVD, respiratory disease and colorectal cancer.